Calf and mid-upper arm circumference as screening tools for sarcopenia in elderly diabetics: evidence from primary healthcare centers - Alif Adlan Zulizar; Nabil Hajar; Lukman Faishal Fatharani; Gita Nurtaningtyas Aini; Tsaqifatul A’izza; Mickhael Sandyka; Muhamad Zidan Akmal Hisani; Bagas Iqbal Pahlevi; Thoha Ibnu Muwaffaq (Folia Medica, 2026)
Abstract Introduction : The bidirectional relationship between sarcopenia and type 2 diabetes mellitus (T2DM) in the elderly creates a detrimental metabolic cycle where insulin resistance accelerates muscle wasting. In resource-limited primary care settings, the lack of advanced diagnostic imaging necessitates the validation of accessible, non-invasive screening tools, such as anthropometric parameters, muscle strength, physical performance, and glycemic control, as surrogate markers for identifying muscle mass depletion. Aim : To evaluate correlations between anthropometric parameters, muscle strength, physical performance, and glycemic control with skeletal muscle mass (SMM) in elderly patients with T2DM. Methods : A cross-sectional study was conducted with 203 elderly T2DM patients at a primary healthcare center. Anthropometric measurements included mid-upper arm circumference (MUAC) and calf circumference (CC). The skeletal muscle mass was measured via bioelectrical impedance analysis, muscle strength via handgrip dynamometry, and physical performance via the timed up and go test (TUGT). Glycemic control data (HbA1c and fasting blood glucose) were retrieved from medical records. Data were analyzed using Pearson and Spearman correlation tests and multiple linear regression. Results : The prevalence of sarcopenia was 41.4%. Multiple linear regression identified CC as the strongest independent predictor of SMM (β=0.370, p =0.000), followed by BMI (β=0.327) and MUAC (β=0.193), with the model explaining 49.6% of SMM variance ( R 2 =0.496). Conclusion : CC and MUAC are valid, low-cost screening alternatives for SMM assessment in resource-limited settings. CC, in particular, serves as a robust indicator for early sarcopenia detection.